Characterization of Intussusception in Qena University Hospital - Eman Saber Ahmed; Nezar Abdelraouf Abo Halawa; Mahmoud Abdelhamid; Mohammed Ahmed Negm (SVU - International Journal of Medical Sciences)
Background: Infants and toddlers have intussusception. Uncontrolled peristalsis or lymphoid hyperplasia after gastrointestinal disease produces ileo-colic, the most frequent kind. Pathologic lead points induce intussusception. Intussusception causes stomach discomfort, bloody feces, and vomiting. Early treatment reduces intestinal blockage, mesenteric vascular dysfunction, and bowel ischemia. Studying paediatric intussusception epidemiology and comorbidities. Objectives: To analyses the epidemiologic features of pediatrics intussusception using the public health data base we also identified comorbidities associated with intussusception. Patients and methods: This prospective observational study documented comprehensive records of 40 cases of intussusception admitted to General Surgery Department, Qena University, and associated hospitals over a period of ten months. Patient information including age, sex, address, presenting symptoms, severity of presentation, investigations performed, laboratory tests, and associated conditions were collected. Management was determined for every case. Results: Fever, vomiting, and abdominal discomfort were the most prevalent symptoms in an intussusception research. 10% had COVID-19. All individuals had ultrasounds, with 42.5% having CT confirmation. 10% had exploration/surgery, 57.5% had conservative management, and 32.5% had hydrostatic reduction. Conservative and hydrostatic treatment had similar rates of recurrence (13 cases). Only 2 recurrences required surgery. Conclusion: This work illuminates pediatric intussusception's epidemiology and comorbidities. Abdominal discomfort and vomiting are most prevalent. Our results emphasize the significance of rapid detection and therapy of intussusception in pediatric patients, particularly those with comorbidities. Explore the pathophysiological causes and risk factors of intussusception in children to guide preventive and early intervention techniques.